Differences in palliative opportunities across diagnosis groups in children with cancer. Issue 1 (15th November 2022) - Ebelhar, Jonathan; DeGroote, Nicholas P.; Massie, A. McCauley; Labudde, Emily; Allen, Kristen E.; Castellino, Sharon M.; Wasilewski‐Masker, Karen; Brock, Katharine E.
Abstract: Background: Childhood cancer causes significant physical and emotional stress. Patients and families benefit from palliative care (PC) to reduce symptom burden, improve quality of life, and enhance family‐centered care. We evaluated palliative opportunities across leukemia/lymphoma (LL), solid tumors (ST), and central nervous system (CNS) tumor groups. Procedure: A priori, nine palliative opportunities were defined: disease progression/relapse, hematopoietic stem cell transplant, phase 1 trial enrollment, admission for severe symptoms, social concerns or end‐of‐life (EOL) care, intensive care admission, do‐not‐resuscitate (DNR) status, and hospice enrollment. A single‐center retrospective review was completed on 0–18‐year olds with cancer who died from January 1, 2012 to November 30, 2017. Demographic, disease, and treatment data were collected. Descriptive statistics were performed. Opportunities were evaluated from diagnosis to death and across disease groups. Results: Included patients ( n  = 296) had LL ( n  = 87), ST ( n  = 114), or CNS tumors ( n  = 95). Palliative opportunities were more frequent in patients with ST (median 8) and CNS tumors (median 7) versus LL (median 5, p  = .0005). While patients with ST had more progression/relapse opportunities ( p  < .0001), patients with CNS tumors had more EOL opportunities ( p  < .0001), earlier PC consultation, DNR status, and hospice enrollment. Palliative opportunities increased toward the EOL in all diseases ( p  < .0001). PC was consulted in 108 (36%) patients: LL (48%), ST (30%), and CNS (34%, p  = .02). Conclusions: All children with cancer incur many events warranting PC support. Patients with ST and CNS tumors had more palliative opportunities than LL, yet received less subspecialty PC. Understanding palliative opportunities within each disease group can guide PC utilization to ease patient and family stress.